PERBANDINGAN PARTISIPASI TENAGA KERJA WANITA INDONESIA DAN TENAGA KERJA WANITA THAILAND - Marieska Lupikawaty (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2013)
The aim of this paper is to know the differents participation women labour market between Thailand and Indonesia. Based on Human Development Index report 2011, position of Indonesia in the medium country with rank 124, then Thailand as the compare due to Thailand as the first rank of Asean country in the same group. The indicator variabel are female employee, distribution unemployment in education, participation married women in labour market, participation women labour in industri. Data were analyzed with kualitatif deskriptif analysis from 1995 until 2008, which the sourced are from International Labour Organization report. The conclusion in general is participation women labour market in Thailand same as rank in HDI index, much larger than in Indonesia. The differents is only on variabel participation labor of married women, Indonesia much larger than Thailand.